Visuomotor imagery as a new tool in the rehabilitation of neglect: a randomised controlled study of feasibility and efficacy - Welfringer, Anouk; Leifert-Fiebach, Gundhild; Babinsky, Ralf; Brandt, Tobias (Disability and rehabilitation, 2011)
Purpose. The aim of this study was to investigate the feasibility of mental practice of positions and movements of the contralesional upper limb in sub-acute neglect patients and the efficacy of the approach in modifying visuospatial and representational neglect symptoms.Method. Fifteen sub-acute neglect patients received two daily half-hour sessions of visuomotor-imagery therapy over a 3-week period as an add-on treatment and were compared to a control group of 15 sub-acute neglect patients without supplementary therapy. Feasibility was assessed using verbal-feedback protocols. Efficacy was determined using various standardised functional-outcome measures and neuropsychological tests.Results. According to therapy protocols, compliance and subjective-gain ratings were high. The results suggest that imagined activation of the contralesional upper limb significantly reduces the severity of neglect in drawing/copying tasks as well as enhancing sensation in the affected arm.Conclusions. We conclude that (i) kinaesthetic visuomotor imagery is a feasible technique for sub-acute neglect patients and that (ii) imagery practice leads to improvements in the perception of body and space. Future research is required to specify criteria for indication and contraindication.